A calculus problem by Karthik Kannan

Calculus Level 4

If the value of

0 e ( x 2 + 1 x 2 ) d x \int_{0}^{\infty} e^{-\left( x^2+\frac{1}{x^{2}}\right)}dx

can be expressed as π a / b c e d \dfrac{\pi^{a/b}}{ce^{d}} where a a , b b , c c and d d are positive integers and a a and b b are coprime, what is the value of a + b + c + d ? a+b+c+d?

Details and Assumptions

  • e e is the base of the natural logarithm.


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ronak Agarwal
Dec 15, 2014

I = 0 e ( x 2 + 1 x 2 ) d x \displaystyle I=\int _{ 0 }^{ \infty }{ { e }^{ -({ x }^{ 2 }+\frac { 1 }{ { x }^{ 2 } } ) }dx }

Put x = 1 t x=\frac{1}{t} and we have d x = 1 t 2 d t dx = - \frac{1}{t^2} \, dt to get (remember to change the limits) :

I = 0 1 t 2 e ( t 2 + 1 t 2 ) d t \displaystyle I = \int _{ 0 }^{ \infty }{ { \frac { 1 }{ { t }^{ 2 } } e }^{ -({ t }^{ 2 }+\frac { 1 }{ { t }^{ 2 } } ) }dt }

Now, put t = x t = x to get

I = 0 1 x 2 e ( x 2 + 1 x 2 ) d x \displaystyle I =\int _{ 0 }^{ \infty }{ { \frac { 1 }{ { x }^{ 2 } } e }^{ -({ x }^{ 2 }+\frac { 1 }{ { x }^{ 2 } } ) }dx }

Adding these two forms we get :

2 I = 0 ( 1 + 1 x 2 ) e ( x 2 + 1 x 2 ) d x = 0 ( 1 + 1 x 2 ) e ( ( x 1 x ) 2 + 2 ) d x \displaystyle 2I=\int _{ 0 }^{ \infty }{ ({ 1+\frac { 1 }{ { x }^{ 2 } } )e }^{ -({ x }^{ 2 }+\frac { 1 }{ { x }^{ 2 } } ) }dx }=\int _{ 0 }^{ \infty }{ ({ 1+\frac { 1 }{ { x }^{ 2 } } )e }^{ -{ (({ x }-\frac { 1 }{ { x } } ) }^{ 2 }+2) }dx }

Put x 1 x = y x-\frac{1}{x} = y and we have d y = ( 1 + 1 x 2 ) d x dy = ( 1+ \frac{1}{x^2} ) \, dx to get our integral as :

2 I = e ( y 2 + 2 ) d y = e 2 e y 2 d y \displaystyle 2I=\int _{-\infty }^{ \infty }{ { e }^{ -{ (y }^{ 2 }+2) }dy } ={ e }^{ -2 }\int _{ -\infty }^{ \infty }{ { e }^{ -{ y }^{ 2 } }dy }

Now the integral left is a standard gaussian integral and it evaluates it to :

2 I = e 2 π 1 2 2I={ e }^{ -2 }{ \pi }^{ \frac { 1 }{ 2 } }

Finally I = π 2 e 2 \large I=\frac { \sqrt { \pi } }{ 2{ e }^{ 2 } }

Nice Solution ! :D

Keshav Tiwari - 6 years, 6 months ago

How do the two intergals equal in step 2?I do not quite understand

毅 荣 - 6 years, 5 months ago

Log in to reply

Just change the variables a definite integral is always same whichever variable you may take.

Ronak Agarwal - 6 years, 5 months ago

Log in to reply

That step wasn't immediately clear (esp due to the abuse of notation), so I separated it out in your solution.

Calvin Lin Staff - 6 years, 1 month ago

t , x t,x are dummy variables.

Tony Zhang - 6 years, 5 months ago

d y = (1 + 1/ x^2) d x

Lu Chee Ket - 5 years, 7 months ago

Almost the same solution

Abhinav Shripad - 1 year, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...